2021
DOI: 10.1002/smll.202104458
|View full text |Cite
|
Sign up to set email alerts
|

Direct Excitation of Triplet State of Molecule by Enhanced Magnetic Field of Dielectric Metasurfaces

Abstract: Efficient excitation of a triplet (T1) state of a molecule has far‐reaching effects on photochemical reaction and energy conversion systems. Because the optical transition from a ground singlet (S0) to a T1 state is spin‐forbidden, a T1 state is generated via intersystem crossing (ISC) from an excited singlet (S1) state. Although the excitation efficiency of a T1 state can be increased by enhancing ISC utilizing a heavy atom effect, energy loss during S1→T1 relaxation is inevitable. Here, a general approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Fabrication of a Silicon Nanodisk Hexagonal Array: Details of the fabrication procedure are described in our previous papers. [31,40] A monolayer of a hexagonal array of polystyrene beads (PSBs) (Polysciences Inc.) with the diameter of 500 nm was formed on an amorphous Si film sputterdeposited on a SiO 2 substrate (SPF-210H, ANELVA). The size of PSBs were then reduced to 450 nm by isotropic etching with oxygen plasma (L-201D, ANELVA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fabrication of a Silicon Nanodisk Hexagonal Array: Details of the fabrication procedure are described in our previous papers. [31,40] A monolayer of a hexagonal array of polystyrene beads (PSBs) (Polysciences Inc.) with the diameter of 500 nm was formed on an amorphous Si film sputterdeposited on a SiO 2 substrate (SPF-210H, ANELVA). The size of PSBs were then reduced to 450 nm by isotropic etching with oxygen plasma (L-201D, ANELVA).…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that enhanced magnetic field of the TD metasurface can strongly enhance spin‐flip direct S 0 →T 1 transition of Ru(II) complexes by photoluminescence excitation (PLE) spectroscopy. [ 31 ] This result indicates that the metasurface can be a platform to promote photochemical reactions utilizing triplet excited states of a molecule.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The structure provides an option of having photon sources with selective excitations of magnetic and electric emission [38] . Such selective excitation can enhance and even monitor certain photochemical reactions, which only happens when magnetic dipole transitions are excited [39,40] . For example, singlet oxygen-mediated photoadditions can be improved through this method.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we aim to extend this work to a more general framework. Furthermore, the inclusion of magnetic interactions or vibronic couplings is an important direction for further manipulation of the molecular excited states. Self-consistent interactions between molecules and light sources may change the excited states. , A stronger interaction between light and molecules to realize hybridized polaritonic states will also be an interesting new avenue of research.…”
mentioning
confidence: 99%